Biochemical properties and oxalate‐degrading activity of oxalate decarboxylase from bacillus subtilis at neutral pH. Issue 7 (26th February 2019) - Conter, Carolina; Oppici, Elisa; Dindo, Mirco; Rossi, Luigia; Magnani, Mauro; Cellini, Barbara
Abstract: Oxalate decarboxylase (OxDC) from Bacillus subtilis is a Mn‐dependent hexameric enzyme that converts oxalate to carbon dioxide and formate. OxDC has greatly attracted the interest of the scientific community, mainly due to its biotechnological and medical applications in particular for the treatment of hyperoxaluria, a group of pathologic conditions caused by oxalate accumulation. The enzyme has an acidic optimum pH, but most of its applications involve processes occurring at neutral pH. Nevertheless, a detailed biochemical characterization of the enzyme at neutral pH is lacking. Here, we compared the structural–functional properties at acidic and neutral pH of wild‐type OxDC and of a mutant form, called OxDC‐DSSN, bearing four amino acid substitutions in the lid (Ser161‐to‐Asp, Glu162‐to‐Ser, Asn163‐toSer, and Ser164‐to‐Asn) that improve the oxalate oxidase activity and almost abolish the decarboxylase activity. We found that both enzymatic forms do not undergo major structural changes as a function of pH, although OxDC‐DSSN displays an increased tendency to aggregation, which is counteracted by the presence of an active‐site ligand. Notably, OxDC and OxDC‐DSSN at pH 7.2 retain 7 and 15% activity, respectively, which is sufficient to degrade oxalate in a cellular model of primary hyperoxaluria type I, a rare inherited disease caused by excessive endogenous oxalate production. The significance of the data in the light of the possible use of OxDC as biological drug is discussed. © 2019 IUBMB Life, 1–11, 2019